Interactive Collaborative Robotics: First International Conference, ICR 2016, Budapest, Hungary, August 24-26, 2016, Proceedings - Ronzhin, Andrey; Rigoll, Gerhard; Meshcheryakov, Roman (Lecture Notes in Computer Science, 2016)
This book constitutes the proceedings of the First International Conference on Interactive Collaborative Robotics, ICR 2016, held in Budapest, Hungary, in August 2016.The 29 papers presented in this volume were carefully reviewed and selected from 48 submissions.